The controversy of social forestry policy: public reaction on the Ministry of Environment and Forestry Decree No. 287/2022/KHDPK in Java, Indonesia - Adib, Mohammad; Abdullah, Irwan; Artaria, Myrtati D.; Rustinsyah, Rustinsyah; Asmorowati, Sulikah; Wardhani, Baiq; Rosnon, Mohd Roslan; Mashud, Musta’in (Taylor and Francis Ltd., 2024)
Social forestry in Java, Indonesia, refers to policies and practices aimed at involving local communities in management and protection of forest areas. The study focuses on the controversy surrounding Decree No. 287/2022/KHDPK of the social forest policy which was rejected by local forest communities and public. The primary contribution of this research is to investigate the reasons behind the rejection on the Ministry of Environment and Forestry regarding Forest Areas with Special Management (KHDPK) policy, particularly the reduction in the forest area it entails. The main stakeholder involved in this controversy include Perum Perhutani, which has a vested interest in maintaining control of 2.4-million-hectare of forest land in Java. A qualitative research method was employed, using a case study approach applied for content analysis. Data were gathered from online newspapers and social media reports published between April 2022 and October 2022. The results indicates that the ongoing controversy reflects a disharmonious relationship between regulators and operators in implementing Agrarian Reform and Social Forestry policies on Java Island. The data suggest that the failure to manage the dialogue between stakeholders can create a challenging environment for the sustainability of both people and forests. Furthermore, involvement of stakeholders in the formulation and implementation of new environmental policies can foster better relationships. This study also highlights the critical role of dialogue and collaboration among regulators, operators, local communities, Non-Governmental Organizations (NGOs), and other stakeholders.